Nondestructive/Noninvasive Imaging Evaluation of Cellular Differentiation Progression During In Vitro Mesenchymal Stem Cell-Derived Chondrogenesis - Correa, Diego (Tissue Eng Part A, 2018)
Chondrogenic cell differentiation constitutes a multistep program that is spatially and temporally modulated by combinations of bioactive factors that drives the establishment of specific cellular phenotypes. This sequence of events results in the fabrication of a distinctive structural and functional extracellular matrix which determines the quality of the cartilaginous tissue and, thus, its potential in vivo implantability as a tissue-engineered implant. Current assessments of engineered cartilage rely on destructive methodologies typically applied at the end of the fabrication period that make it difficult to predict failures early in the process. The high inherent variability of engineered tissues raises questions regarding reproducibility and the validity of using such end-stage representative samples to characterize an entire batch of engineered tissues. Therefore, the development of dynamic, multimodal, nondestructive, and noninvasive technology toolsets to monitor cell differentiation (and secondarily tissue phenotypes) in real time is of paramount importance. In this study, we report the creation of cell-based probes to directly interrogate cell differentiation events during in vitro chondrogenesis and in vivo osteogenesis. For that, native promoters of well-established chondrogenic (Sex Determining Region Y-Box 9 [Sox9] and Aggrecan [AGG]) and osteogenic (Osteocalcin [OC]) differentiation biomarkers were used to create independent probes incorporating a traceable signal (Luciferase) and transduced into human bone marrow-derived mesenchymal stem cells. The probes were used to monitor the progression throughout in vitro chondrogenic differentiation program in aggregate (pellet) cultures and in vivo osteogenic differentiation in heterotopic ossicles. These tissue differentiation constructs were positively tested in conditions known to modulate the differentiation program at various phases that confirmed their sensitivity and reproducibility. This technology toolset allows a nondestructive and noninvasive, imaging-based longitudinal reconstruction of the in vitro chondrogenic differentiation program, while providing an analytical assessment of phenotypic changes of engineered cartilage in real time.